Teachers' Strategies for Motivating Grade III Students with Learning Difficulties at SD Alkhairaat Mamboro - Wanda Visqiyah; Abdul Rahman; Nuraini Nuraini; Azizah Azizah; Sukri Sukri (FKIP - Universitas Riau, 2026)
Learning difficulties may affect elementary school students’ classroom engagement and participation, highlighting the need for adaptive instructional practices. This study aimed to describe the instructional strategies employed by a Grade III teacher to support students experiencing learning difficulties and to explore their learning responses. A qualitative descriptive approach was conducted in one Grade III classroom at SD Alkhairaat Mamboro, Indonesia, involving one teacher and students as the context of observation. Data were collected through classroom observations, semi-structured interviews, and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the teacher employed adaptive instructional strategies, including simple and age-appropriate language, classroom management, individualized guidance, instructional media, collaborative group work, interactive questioning, and positive reinforcement through praise and rewards. These strategies were associated with positive learning responses, including greater attention, active participation, willingness to complete learning tasks, and confidence in answering questions. The findings suggest that these practices were observed alongside a supportive classroom environment that encouraged student participation and engagement. Given the qualitative descriptive design, the findings are context-specific and do not establish a causal effect on students’ learning motivation.